Dynamic Capabilities and Strategic Management - Teece, David J. (HighBridge, 2019)
How do firms compete? How do firms earn above normal returns? What's needed to sustain superior performance long term? An increasingly powerful answer to these fundamental questions of business strategy lies in the concept of dynamic capabilities. These are the skills, processes, routines, organizational structures, and disciplines that enable firms to build, employ, and orchestrate intangible assets relevant to satisfying customer needs, and which cannot be readily replicated by competitors. Enterprises with strong dynamic capabilities are intensely entrepreneurial. They not only adapt to business ecosystems; they also shape them through innovation, collaboration, learning, and involvement. This book is the clearest and most succinct statement of the core ideas of dynamic capabilities. David Teece, the pioneer of the dynamic capabilities perspective, explains their genesis, application, and how they offer an alternative approach to much conventional strategic thinking grounded in simplistic and outdated understandings of industrial organizations and the foundations of competitive advantage. Accessibly written and presented, it will be an invaluable and stimulating tool for all those who want to understand this important contribution to strategic thinking, be they Mba students, academics, managers, or consultants.